Energy Demand and Supply Issues - Scenario 2020 and Implications for CDM in West African Economic and Monetary Union. Case Study: Benin, Burkina Faso, Niger and Togo - Honorat Satoguina (Hamburg Institute of International Economics (HWWA), 2006)
The present study discusses energy supply challenge and assesses renewable energy potential in the studied countries. Moreover, energy demand as well as demand projection is assessed until 2020. Resulting CO2-eq emissions are also projected. The study reveals that the countries under examination lack accurate information on their renewable energy potentials. Based on cautious assumptions, countries renewable energy potentials have been assessed. Solar sources and biomass are not assessed. The study shows that countries are endowed with low renewable energy potentials. Using GDP per capita and population grow as driving forces, countries' electricity demands are projected until 2020. As result, electricity demand in case study countries will not be very high, as economic development is projected to remain low. Consequently, despite an increase in CO2 emissions, emissions will remain at a low level. Hence, the countries studied cannot be as competitive as current competing CDM countries, i.e., China, India, Brazil, etc. Strengthening energy co-operation within West African Economic and Monetary Union may reduce transaction costs, making it possible to use the available energy potential.
Keywords: C87; Q43; Q41; C89; C69; C53; C40; C22; 330; Renewable energy potential; Energy supply and demand; energy demand scenarios; CDM market